Pengaruh Perputaran Piutang dan Perputaran Persediaan terhadap Return on Asset pada Perusahaan Otomotif dan Komponen Periode 2013-2018 - Evi Fujilestari; Radia Purbayati; Fatmi Hadiani (Indonesian Journal of Economics and Management, 2020)
The purpose of this research is to test the effect of receivable turnover and inventory turnonver toward Return On Asset (ROA). The research sample are used Automotive Companies Listed on Indonesia Stock Exchange Period 2013 – 2018, using purposive sampling method are 6 companies. The data are used secondary data from financial statement of companies published by Indonesia Stock Exchange through the official website of Indonesia Stock Exchange namely www.idx.co.id. Analyse technique are used the multiple linear regression with EViews of 10 version. The results showed that receivable turnover has no significant effect on ROA with significance value greater than 0.05, which is 0.8201, inventory turnover is positive and significant with significance value smaller than 0.05, which is 0.0065.